2011
DOI: 10.2984/65.2.235
|View full text |Cite
|
Sign up to set email alerts
|

Community Composition of Elasmobranch Fishes Utilizing Intertidal Sand Flats in Moreton Bay, Queensland, Australia

Abstract: Thirteen elasmobranch species were collected during a 4-yr survey of the intertidal margins of Moreton Bay, a large subtropical embayment in southeastern Queensland, Australia. Stingrays were the most common large predators in the intertidal zone, with total catch dominated numerically by blue-spotted maskray, Neotrygon kuhlii (53.8%); estuary stingray, Dasyatis fluviorum (22.2%); and brown whipray, Himantura toshi (10.2%). There was a significant female bias within intertidal populations of N. kuhlii and D. f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…The capture of 13 species of Carcharhiniformes in this study equalled the number reported for a tropical bay in the Gulf of Carpentaria, Australia (Blaber et al , 1995) and was higher than those reported in Cleveland Bay, Australia (12 species; Simpfendorfer & Milward, 1993) and Herald Bight, Shark Bay, Western Australia (White & Potter, 2004). Shallow regions of Moreton Bay also provide habitat for numerous species of rays, including the blue‐spotted maskray Neotrygon kuhlii (Müller & Henle 1841) and the estuarine stingray Dasyatis fluviorum Ogilby 1908 which are abundant in intertidal regions (Pierce et al , 2011). The abundance of sharks and rays in shallow regions of Moreton Bay suggest that they may influence the structure of the local ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…The capture of 13 species of Carcharhiniformes in this study equalled the number reported for a tropical bay in the Gulf of Carpentaria, Australia (Blaber et al , 1995) and was higher than those reported in Cleveland Bay, Australia (12 species; Simpfendorfer & Milward, 1993) and Herald Bight, Shark Bay, Western Australia (White & Potter, 2004). Shallow regions of Moreton Bay also provide habitat for numerous species of rays, including the blue‐spotted maskray Neotrygon kuhlii (Müller & Henle 1841) and the estuarine stingray Dasyatis fluviorum Ogilby 1908 which are abundant in intertidal regions (Pierce et al , 2011). The abundance of sharks and rays in shallow regions of Moreton Bay suggest that they may influence the structure of the local ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…Stingrays are viviparous (Hamlett and Hysell, 1998) and only the active movement of juveniles or adults potentially translates into gene flow, thus partly explaining a possible higher level of genetic differentiation in N. kuhlii than generally observed in coastal benthic teleosts where an IBD pattern has been observed. This is further supported by tagging experiments in N. kuhlii, which indicate this as a sedentary species (Pierce et al, 2011).…”
Section: Investigating Mechanisms Of Genetic Differentiationmentioning
confidence: 91%
“…In this study, we investigated ontogenetic shifts in brain size and brain organization in one species of batoid chondrichthyan, i.e., the bluespotted stingray Neotrygon kuhlii (Müller and Henle, 1841). This relatively small species of stingray is common in shallow coastal and estuarine habitats in Southeast Queensland, Australia [Last and Stevens, 1994;Pierce et al, 2009Pierce et al, , 2011. Although a preliminary analysis using a small number of individuals has suggested ontogenetic shifts in the brain of N. kuhlii , here we present a far more comprehensive assessment of ontogenetic shifts in relative brain size, the relative development of seven major brain areas, and cerebellar foliation and cerebellar asymmetry across a much larger data set that encompasses the full postpartum developmental range in this species.…”
Section: Introductionmentioning
confidence: 99%